Peningkatan Efisiensi Pendistribusian Barang Melalui Optimasi Pengalokasian Moda Transportasi Darat Pada PT. X - Felicia Saputra; I Gede Agus Widyadana (Jurnal Titra, 2015)
This research is originated from the current efficiency level of product distribution in PT. X which is considered low. This motivates the company to consider other transportation to distribute their products, which is train. PT. X sees train as a new opportunity as now there is double track in the system. On the other hand, train tends to have cheaper delivery costs than truck as the delivery distance increase. Method used to analyze the efficiency of both transportations is simulation. Observation has been made and the results shows that 50,55% of delivery route in Java and 77,97% of delivery route from Java to Sumatera can be replaced by train. Improvement and solution has also been proposed as a support for train distribution system so that the increase of overall efficiency can be achieved. The analyze of the system improvement shows result that the use of two point railway stations will reduce overall cost by 4,70%, while the use of three point railway stations will save overall costs by 5,02%.